Removal of Cr(vi) from wastewater by a two-step method of oxalic acid reduction-modified fly ash adsorption. Issue 58 (22nd October 2019) - Jiang, Xiaoling; Fan, Wenqiang; Li, Chunqing; Wang, Yong; Bai, Junbin; Yang, Hongjian; Liu, Xiaoli
Abstract : Removal of Cr(vi ) from wastewater using a two-step method. Abstract : Excessive Cr(vi ) emissions have been and continue to be a major contributor to heavy-metal pollution; recently, the development of a low-cost, safe and efficient method for the removal of Cr has attracted significant attention. In the present study, a two-step method involving oxalic acid reduction and modified fly ash adsorption was developed. The experimental results showed that this methodology exhibited high Cr(vi ) removal efficiency under the following conditions: 1.5 g L −1 of oxalic acid, modification of fly ash (FA) by 20 wt% KOH, a contact time of 2 h and a mass of 0.3 g of modified fly ash (MFA) at room temperature (15–25 °C). The influencing factors of the adsorbent were discussed by characterized for their elemental composition, functional groups, surface area and surface morphology. According to the characteristic parameters and q e, the isothermal adsorption process could be well-described by the Langmuir model. The adsorption process resembles more closely to the pseudo-second-order kinetic model. In conclusion, this two-step method of oxalic acid reduction-modified fly ash adsorption is promising for Cr(vi ) removal.